The Use of Digital Open Systems in the Preparation of Students - Предик, Аліна Анатоліївна (IJCSNS International Journal of Computer Science and Network Security, 2022)
The main purpose of the article is to study the process of using digital open systems in student training. The development of information and communication technologies (ICT) and their integration into all spheres of human activity and society affect the nature of production, scientific research, education, culture, life, social relations and other processes. Given this, a digital transformation of social development is taking place, in particular, the digitalization of education is an imperative for reforming the educational industry, the main and primary task of the effective development of the information society in the world. As a result of the study, the current state of the use of innovative information and communication technologies in the process of preparing students, as well as the use of an open educational environment as an advanced means of developing the pedagogical environment and higher education, was analyzed.
The Use of Digital Open Systems in the Preparation of Students
Keywords: communication technologies, scientific research, education, culture, life, social relations and other processes.